1996
DOI: 10.1136/fn.74.2.f88
|View full text |Cite
|
Sign up to set email alerts
|

Early determinants of right and left ventricular output in ventilated preterm infants.

Abstract: One hundred and twenty ventilated preterm infants, birthweight <1500 g, were examined within the first 36 hours with colour Doppler echocardiography, to determine the cardiorespiratory influences on right (RVO) and left ventricular output (LVO). Forty nine of these infants had three further daily scans. Measurements included left ventricular (LV) ejection fraction, Doppler determination of RVO and LVO, and ductal and interatrial shunt direction, velocity and colour Doppler diameter. Infants were grouped by res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
182
4
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(201 citation statements)
references
References 34 publications
(14 reference statements)
10
182
4
5
Order By: Relevance
“…Poor myocardial function is common in these preterm infants, 21 and may be mediated by hypoxia and/or ischemia. 1 Infants requiring inotropes had higher cTnT compared to those who were normotensive but this did not reach statistical significance possibly due to the relatively small number of subjects. Clark SJ et al 18,22 showed a similar effect of inotropes on cTnT levels.…”
Section: Biochemical Markers and Preterm Infants A El-khuffash Et Almentioning
confidence: 82%
See 3 more Smart Citations
“…Poor myocardial function is common in these preterm infants, 21 and may be mediated by hypoxia and/or ischemia. 1 Infants requiring inotropes had higher cTnT compared to those who were normotensive but this did not reach statistical significance possibly due to the relatively small number of subjects. Clark SJ et al 18,22 showed a similar effect of inotropes on cTnT levels.…”
Section: Biochemical Markers and Preterm Infants A El-khuffash Et Almentioning
confidence: 82%
“…The higher cTnT levels in infants with RDS may therefore reflect the previously reported association between RDS and poor myocardial performance. 1 There was no relationship between cTnT and PDA diameter or LA:Ao suggesting that cTnT is less influenced by volume loading of the heart. N-terminal-pro-natriuretic peptide NTpBNP levels were not influenced by gestation, birth weight, gender, mode of delivery or antenatal factors.…”
Section: Biochemical Markers and Preterm Infants A El-khuffash Et Almentioning
confidence: 89%
See 2 more Smart Citations
“…A previous study has shown that preterm infants have a significantly higher cerebral OEF on the first day after birth when compared with day 2 (Kissack et al, 2004). Left ventricular output (LVO) increases during the days after birth (Evans and Kluckow, 1996) and there is a significant correlation between cerebral OEF and LVO on the first day after birth (Kissack et al, 2004). The likely mechanism that links low LVO and increased cerebral OEF is that low LVO causes reduced cerebral oxygen delivery, but this has not previously been established.…”
Section: Introductionmentioning
confidence: 99%